Investigating the relationship between land use and soil moisture variation in Suid Bokkeveld, South Africa - Umulisa, Viviane (Department of Environmental and Geographical Science, 2016)
This study investigated the spatial variability of soil moisture as well as changes within the soil profile of different land use types in the Suid Bokkeveld, situated to the south-west of the Nothern Cape, South Africa. This area has been experiencing harsh weather conditions that affect local agricultural production and multiple livelihood activities. The primary aim of the research was to analyse the influence of land use adopted in response to weather and climate change by studying the effects of soil moisture variations in the area. The study found that, together with depth and soil particle size, different types of land use contribute to soil moisture variations. Out of the five types of land uses that were investigated, rooibos cultivated farms had the highest soil moisture variability. The second highest variability was found in grazing cultivated farms and the lowest in natural and grazing never cultivated land, respectively. The results confirm that the shift from rooibos tea and wheat cultivation to grazing has contributed to a reduction in soil moisture variations. The grazing cultivated and fallow system could therefore be an effective land use types to ensure water and soil conservation, reduce land degradation and adapt to weather and climate change. The significance of this study lies in it being one of the first explorations into soil moisture in this area. Other forcing factors will need to include building a comprehensive and integrated understanding of soil moisture variability based on multiple influencing factors.